Experimental and numerical heat transfer investigation in a tubular heat exchanger with delta-wing tape inserts - Skullong, Sompol; Promvonge, Pongjet; Jayranaiwachira, Nuthvipa; Thianpong, Chinaruk (My University, 2016)
Effects of insertion of a straight tape with double-sided delta wing pairs (called “delta-wing tape”, DWT) used as a longitudinal vortex generator (LVG) on forced convective heat transfer and flow friction characteristics in a uniform heat-flux heat exchanger tube are investigated experimentally and numerically in the present work. The experiment is conducted for turbulent airflow with the Reynolds number (Re) from 4200 to 25,500. The delta wings are in a forward-wing arrangement with three wing inclination angles (α = 30°, 45° and 60°) and with five ratios of wing-pitch to tube-diameter (P/D = PR = 0.5, 1.0, 1.5, 2.0 and 2.5). Influences of the DWT insert on heat transfer in terms of Nusselt number (Nu) and pressure drop in the form of friction factor (f) are examined. The results indicate that the DWT provides the increases in Nu and f up to 505% and 69 times above the plain tube, respectively and the maximum thermal enhancement factor (TEF) is at 1.49. The 60° DWT with PR = 0.5 yields the highest Nu and f but the 30° one with PR = 1.0 gives the best TEF. To understand the flow structure and heat transfer mechanism, a three dimensional CFD simulation of the inserted tube is also performed. The simulated results are validated and are in good agreement with the current measurements. A simulated heat transfer and fluid flow structure is also reported.
Keywords: Delta wing tape; Fluid flow; Heat exchanger; Thermal performance; Vortex generators